Ozônio flotação na colheita de microalgas cultivadas em efluente sanitário - Oliveira, Gislayne Alves (2018)
The lack of treatment of sanitary effluents causes several problems, both public health and environmental problems. And it can be reduced by using this sanitary effluent as a source of nutrients for microalgae growth. In addition to providing water treatment, reduce costs, microalgae can also be used for various purposes, such as the production of biofuels. However, one of the major challenges for the use of microalgae is the harvest method, as it is not cost-effective. Among the harvest methods are coagulation/flocculation and ozone flotation. The first is a low-cost harvesting method, but requires the addition of coagulants, usually with metals, that can cause contamination of the harvested biomass by restricting its subsequent use. The ozone flotation adds the physical properties of the flotation and the oxidizing action of the ozone that in contact with the cells propitiates the harvest, liberate biomolecules, including the proteins that are considered biosurfactantes reducing the possibility of coalescence of the ozone bubbles. The formation of bubbles is one of the most important parameters in flotation because they influence the reaction time in the column, the probability of collision and capture of the microalgae. The general objective of the present work was to evaluate parameters that influence ozone flotation in a three - phase system (sanitary effluent - microalgae - ozone bubbles) aiming at the separation of microalgae grown in residual water for biofuel generation. Also, for ozone flotation, the influence of ozone flow, column height and initial biomass concentration on the size of the ozone bubbles in a three - phase system (sanitary effluent - microalgae - ozone) was determined. The results showed that the microalgae Scenedesmus obliquus grown in a high-rate reactor is efficient in the removal of nutrients from the residual water, obtaining complete removal of ammoniacal nitrogen and removal of 93% for total nitrogen and 61% of orthophosphate. As for the comparison between coagulation/flocculation and ozone flotation, the best results of water quality for most parameters (NH3-N, NTK, nitrate and nitrite) were obtained in the ozone harvest, except for orthophosphate. It was also obtained the highest recovery of lipids, carbohydrates and proteins that were 0,32 ± 0,03, 0,33 ± 0,025 and 0,58 ± 0,014 mg/mg of biomass. Unlike coagulation/flocculation, there was a lower recovery of 0.21 mg of lipids/mg of biomass and 0,12 – 0,23 mg of protein/mg of biomass. Concerning the efficiency of harvesting for coagulation/flocculation up to 98% was obtained using 2 g of aluminum sulfate/L and for ozone flotation it was obtained up to 91.5% when an O3 dose of 0,16 mg of O3/mg of biomass was applied. The ozone flow, the height in the column to which the images were captured and the initial concentration of microalgae directly interfere with the size of the bubbles, as well as the oxidation of the microalgae cells and the transfer of O3. The action of the proteins as biosurfactants reduced the size of the bubbles, ie, the higher the initial biomass concentration in the column the higher the protein release and thus the lower the bubble sizes obtained for all ozone flows (0.2, 0.6 and 1 L/min).